2007
DOI: 10.1136/jnnp.2006.112987
|View full text |Cite
|
Sign up to set email alerts
|

Voxel based analyses of diffusion tensor imaging in Fabry disease

Abstract: Background: Fabry disease (FD) is a lysosomal storage disorder associated with marked cerebrovascular disease. Conventional MRI shows an extensive load of white matter lesions (WMLs) which may already be present at an early stage in the disease. Objective: Investigator independent and sensitive quantification of structural changes in the brain in clinically affected men and women with FD. Methods: We performed a voxel based analysis of diffusion tensor images (DTI) in 25 patients with FD and 20 age matched nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 35 publications
7
50
0
1
Order By: Relevance
“…Standard CNS imaging modalities include computed tomography (CT) and MRI (Table 2). 13,88,126,[130][131][132] Contrast media are usually not required. The MRI protocol should include: T1-weighted; fluid attenuated inversion recovery/T2-weighted; T2*/susceptibility; and diffusion-weighted imaging sequences.…”
Section: Neuroimaging Techniques In Patients With Fdmentioning
confidence: 99%
See 2 more Smart Citations
“…Standard CNS imaging modalities include computed tomography (CT) and MRI (Table 2). 13,88,126,[130][131][132] Contrast media are usually not required. The MRI protocol should include: T1-weighted; fluid attenuated inversion recovery/T2-weighted; T2*/susceptibility; and diffusion-weighted imaging sequences.…”
Section: Neuroimaging Techniques In Patients With Fdmentioning
confidence: 99%
“…Currently, many asymptomatic Fabry patients are not being monitored regularly, but increasing awareness of the importance of silent infarcts and other stroke risk factors from the general stroke population should encourage neurologists to monitor Fabry patients for signs of early CNS involvement periodically, at least on a clinical basis, using appropriate imaging studies when indicated (Table 2). 13,88,126,[130][131][132] Other imaging techniques, such as DTI and 3-dimensional T1-acquisition, are not used as routine investigations for patients with FD, but can provide useful clinical information (Table 2). 13,88,126,[130][131][132] Of note, voxel-based analysis of DTI images has been shown to be an investigator-independent and sensitive tool for evaluating early white matter injury in patients with FD, allowing direct comparison with control subjects.…”
Section: Neuroimaging Techniques In Patients With Fdmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of fiber bundles observed by FA images was basically identical to that of the real fiber bundles (4). The voxel analysis of FA value can sensitively reflect brain lesions to a certain degree (6,7). The structure of fiber bundles of lumbosacral nerve roots is identical to that of intracranial nerve fibers, so their imaging principles are identical.…”
Section: Discussionmentioning
confidence: 71%
“…Since Clark et al (5) applied DWI in the spinal cord in 1999, the application of DTI in the spinal cord already has certain initial experience from ex vivo; in vivo animal to human. DTI is sensitive to the appearance of disease, but currently, studies on spinal cord DTI are scarce (6,7). This is mainly due to the special structure of the spinal cord.…”
Section: Introductionmentioning
confidence: 99%